Magnetoelastic plane waves in rotating media in thermoelasticity of type II (G-N model) - S. K. Roychoudhuri; Manidipa Banerjee (Chattopadhyay) (International Journal of Mathematics and Mathematical Sciences)
A study is made of the propagation of time-harmonic plane waves in an infinite, conducting, thermoelastic solid permeated by a uniform primary external magnetic field when the entire medium is rotating with a uniform angular velocity. The thermoelasticity theory of type II (G-N model) (1993) is used to study the propagation of waves. A more general dispersion equation is derived to determine the effects of rotation, thermal parameters, characteristic of the medium, and the external magnetic field. If the primary magnetic field has a transverse component, it is observed that the longitudinal and transverse motions are linked together. For low frequency (χ≪1, χ being the ratio of the wave frequency to some standard frequency ω∗), the rotation and the thermal field have no effect on the phase velocity to the first order of χ and then this corresponds to only one slow wave influenced by the electromagnetic field only. But to the second order of χ, the phase velocity, attenuation coefficient, and the specific energy loss are affected by rotation and depend on the thermal parameters cT, cT being the nondimensional thermal wave speed of G-N theory, and the thermoelastic coupling εT, the electromagnetic parameters εH, and the transverse magnetic field RH. Also for large frequency, rotation and thermal field have no effect on the phase velocity, which is independent of primary magnetic field to the first order of (1/χ) (χ≫1), and the specific energy loss is a constant, independent of any field parameter. However, to the second order of (1/χ), rotation does exert influence on both the phase velocity and the attenuation factor, and the specific energy loss is affected by rotation and depends on the thermal parameters cT and εT, electromagnetic parameter εH, and the transverse magnetic field RH, whereas the specific energy loss is independent of any field parameters to the first order of (1/χ).